Breaking open the case of one patient's acute left flank pain: nutcracker syndrome - Rebecca Bajkowski; Anthony Lagina (Journal of the American College of Emergency Physicians Open)
Abstract Acute flank and abdominal pain represent a common presenting complaint in the emergency department. The etiology can be broad, ranging from the chest to the groin, from benign to catastrophic. There are common causes such as nephrolithiasis and pyelonephritis for which more than 1 million Americans are diagnosed with in the United States each year.1 Other etiologies are more rare and difficult to diagnose. The following case discusses a rare syndrome involving a young man with flank pain and a few other symptoms.